Video‐Based Interaction, Negotiation for Comprehensibility, and Second Language Speech Learning: A Longitudinal Study. Issue 1 (15th June 2016) - Saito, Kazuya; Akiyama, Yuka
Abstract: This study examined the impact of video‐based conversational interaction on the longitudinal development (one academic semester) of second language production by college‐level Japanese English‐as‐a‐foreign‐language learners. Students in the experimental group engaged in weekly dyadic conversation exchanges with native speakers in the United States via telecommunication tools. The native speaker interlocutors were trained to provide interactional feedback (recasts) when the nonnative speakers' utterances hindered successful understanding (i.e., negotiation for comprehensibility). The students in the comparison group received regular foreign language instruction without any interaction with native speakers. The coded video data showed that the experimental students worked on improving all linguistic domains of language, likely in response to their native speaker interlocutors' interactional feedback (recasts, negotiation) during the treatment. The pretest–posttest data of the students' spontaneous production showed that they made significant gains in the dimensions of comprehensibility, fluency, and lexicogrammar but not in those of accentedness and pronunciation. Open Practices: This article has been awarded an Open Materials badge. All materials are publicly accessible in the IRIS digital repository athttp://www.iris‐database.org . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .